Rethinking MOOCs: The Promises for Better Education in India - Nemer, David; O'Neill, Jacki (International Journal of Information Communication Technologies and Human Development, 2019)
Indian users are the second largest population enrolled in MOOCs; yet little is known about them. In this qualitative study of MOOC users in India, the authors aim to understand how and why they use MOOCs. The findings show how MOOCs fit into the Indian context, specifically how they compare to the interviewees’ educational experiences and the trade-off between language and content. This article also examines a group of ex-users, that is, a group of previous users who have turned away from MOOCs despite having an educational need. Furthermore, it highlights how the findings contribute to the debate on MOOCs and the promise for better education. Proponents of MOOCs have claimed that they are an improving force for education because they provide free access for anyone with an internet connection to high-quality teachers and materials on a scale not possible before. The authors use the emergent themes from the data to challenge these claims.